Intermittent outpatient administration of levosimendan improves right ventricular-pulmonary arterial coupling in ambulatory patients with advanced heart failure. (8th February 2021) - Melillo, E; Masarone, D; Valente, F; Vastarella, R; Gravino, R; Ammendola, E; Verrengia, M; Caiazzo, A; Petraio, A; Pacileo, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Intermittent infusions of levosimendan in an outpatient setting have been associated with improved symptoms and reduced hospitalizations in patients with advanced heart failure (HF). Little is known on the potential effect of intermittent levosimendan infusions on right ventricle (RV)-pulmonary arterial (PA) coupling in ambulatory patients with advanced HF. Purpose Aim of the present study was to explore the effects of intermittent levosimendan infusions on the ratio between tricuspid annular plane systolic excursion (TAPSE) and pulmonary artery systolic pressure (PAPs), an echocardiographic measure of RV/PA coupling, in ambulatory patients with advanced HF, and on left ventricular arterial coupling (VAC), expressed as the relationship between arterial elastance (Ea) and ventricular elastance (Ees). Methods 17 ambulatory patients with advanced HF treated with intermittent levosimendan (6-hour intravenous infusion, 0.2 ug/kg/min without bolus) received baseline clinical, biochemical and echocardiographic evaluation and changes in TAPSE/PAPs ratio were assessed from baseline to 48 hours after the infusion, based on the pharmacokinetic profile of levosimendan. VAC, expressed as Ea/Ees ratio, was obtained by a calculator (iElastance) designed for non-invasive single beat measure of end-systolic Ees  and Ea according to Chen"s method. Results After 48 hours from levosimendan infusion, there was a significant improvement of TAPSE/PAPs  ratio (p = 0.04), stroke voume (SV) (p = 0.05) and cardiac output (CO)(p = 0.04). We observed a significant reduction of Ea (p = 0.007) and of Ees (p = 0.01) and a non significant improvement of VAC (p = 0.4)(Tab.1).  Conclusion. Our results show that an intermittent 6-hour levosimendan infusion at 0.2 ug/kg/min improves after 48 hours RV-PA coupling, SV, CO, Ea and Ees in ambulatory patients with advanced HF. Further studies including more patients are necessary to confirm these preliminary findings.